Perencanaan Teknis Operasional Pengelolaan Sampah Di Permukiman Padat Penduduk (Kelurahan Kota Bambu Selatan) - Mayang Nuur Ervani; Dwi Indrawati; Pramiati Purwaningrum (Universitas Trisakti, 2021)
In 2019 the West Jakarta Administrative City was recorded to be able to produce 700 tons of waste per day. The existence of a high level of population density causes problems in waste management operations to also increase. Especially in the procurement of land, facilities and infrastructure for waste management. The purpose of this planning is to plan an effective and efficient waste management system through the 3R concept (Reuse, Reduce, Recyle) in densely populated residential areas. The method used is based on SNI 19-3964-1994 concerning Methods for Taking and Measuring Samples of Generation and Composition of Municipal Waste. Waste management planning which includes packaging, collection, removal, processing, and final transportation will be planned for 20 years (2020-2040) through three stages of planning. Based on the sampling results, the amount of waste generated in Kelurahan Kota Bambu Selatan was 152 liters/day with a waste generation rate of 1.5 liters / person / day. The composition of the waste consists of 64.97% organic and 35.03% non organic. The planned waste reduction potential is 70% with a target of 30% of the amount of waste entering the TPST. The main components in 3R-based planning are reducing waste at the source and increasing the potential for waste reduction through waste banks and 3R TPS.